Experiencias ecológicas del Colegio de la Inmaculada-Jesuitas - Carbajal Alva, Max Alberto (2009)
This article presents a brief systematization about a pioneer experience of Colegio de la Inmaculada-Jesuitas, a private catholic school located in Lima (Peru) in relation to its environmental projects developed as part of its institutional policy since several decades ago. This experience has deserved public acknowledgement by other Peruvian institutions.